Pengaruh Akuntabilitas Alokasi Dana Desa, Transparansi, dan Partisipasi Masyarakat Terhadap Pembangunan Desa di Desa Jati Kesuma Kecamatan Namorambe Kabupaten Deli Serdang - Meutia Larasati; Warsani Purnama Sari; Aditya Amanda Pane (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to examine the influence of accountability in village fund allocation, transparency in village governance, and community participation on village development in Jati Kesuma Village, Namorambe Subdistrict, Deli Serdang Regency. The research employed a quantitative approach with a total of 90 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using multiple linear regression. The results indicate that all three independent variables—accountability, transparency, and community participation—have a positive and significant effect on village development, both partially and simultaneously. Among them, community participation was found to have the most substantial contribution. These findings highlight the importance of good governance practices in village financial management, particularly in promoting participatory development and transparency to enhance sustainable rural development.